Effectiveness of capsules installation containing paraffin wax in a solar water heater - Muhammad Nadjib; Wahyudi Wahyudi; Fajar Anggara; Yosua Heru Irawan (SINERGI, 2022)
The encapsulation technique is one way to use latent heat storage material in a solar water heater tank. In this technique, several capsules may be arranged in the tank. In this study, the capsules were installed along the cross-section of the tank. There has been no discussion of which part of the capsule position has optimal heat energy with a capsule arrangement. Proper placement of the capsule arrangement can result in optimal thermal energy storage in the tank. This study aimed to investigate the effectiveness of installing capsules in a tank with different positions in terms of thermal energy storage. The study used an active solar water heater. The 24 capsules containing paraffin wax were arranged in a tank. The solar simulator was used as a heat source for the collector, and it was set at 1000 W/m2. The flow rate of water was 2 liters/minute. During the charging process, the water and paraffin wax temperature was recorded. The temperature evolution of water and paraffin wax obtained were used to analyze the thermal energy content. The results showed that the average heating rate for water and paraffin wax was 0.246 °C/min and 0.254 °C/min, respectively, so the capsule arrangement served as a suitable heat exchanger. The capsules installed at the top had an average heating rate increase of 111.4% compared to those at the bottom. Therefore, mounting the capsule at the top of the tank was more effective than placing it at the bottom.